Chemical characterization of polysaccharides from Baccharis trimera (Less.) DC. infusion and its hepatoprotective effects. (October 2020) - Chaves, Pedro Felipe Pereira; Adami, Eliana Rezende; Acco, Alexandra; Iacomini, Marcello; Cordeiro, Lucimara Mach Côrtes
Graphical abstract: Highlights: Baccharis trimera tea is traditionally used for the treatment of hepatic disorders. Polysaccharides from B. trimera tea were characterized and the fructan inulin was found. In vitro, inulin at 300 μg/mL, was able to scavenger 97% of the DPPH radicals. In vivo, at low dose (1 mg/kg) inulin protected the liver against CCl4 -induced injuries. Inulin is an hepatoprotector compound found in B. trimera tea. Abstract: Baccharis trimera is a native medicinal plant from South America popularly known as "carqueja". Its infusion is traditionally ingested for the treatment and prevention of hepatic disorders. Up to now, only the crude aqueous extract or hydroethanolic fractions, containing the secondary metabolites, have been studied and correlated with their biological action on the liver. Here we report that an inulin type fructan is present in the B. trimera infusion and contributes to the hepatoprotective effect of the species. In vitro, inulin at 300 μg/mL, was able to scavenger 97% of the DPPH radicals. In vivo experiments showed that it protected the liver against CCl4 -induced injuries. The administration of inulin at low dose of 1 mg/kg significantly reduced the blood levels of ALT, AST and ALP, reduced the lipid peroxidation and increased the catalase activity and the levels of reduced glutathione in the liver of CCl4 -treated mice. Moreover, the administration of inulin at 100 mg/kg increased GSH levels in the liver of Naïve mice. No signs of toxicity were observed. Thus, inulin present in B. trimera infusion protects the liver from the oxidative stress caused by CCl4 administration and can corroborate with the hepatoprotective effects presented by the species infusion.